2016
DOI: 10.1016/j.chemosphere.2016.08.089
|View full text |Cite
|
Sign up to set email alerts
|

Multiple elemental exposures amongst workers at the Agbogbloshie electronic waste (e-waste) site in Ghana

Abstract: Electronic waste (e-waste) recycling is growing worldwide and raising a number of environmental health concerns. One of the largest e-waste sites is Agbogbloshie (Ghana). While several toxic elements have been reported in Agbogbloshie’s environment, there is limited knowledge of human exposures there. The objectives of this study were to characterize exposures to several essential (copper, iron, manganese, selenium, zinc) and toxic (arsenic, cadmium, cobalt, chromium, mercury, nickel, lead) elements in the uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 17 publications
9
94
3
1
Order By: Relevance
“…Urine was collected in sterile cups and samples were aliquot an hour after collection, frozen at -20 degrees Fahrenheit, and then moved to -70 degree Fahrenheit freezer for storage. The UCd was determined as previously described (Basu et al 2010; Srigboh et al 2016). Briefly, 0.5 mL of sample was digested with an equal volume of concentrated nitric acid and allowed to sit overnight in a fume hood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine was collected in sterile cups and samples were aliquot an hour after collection, frozen at -20 degrees Fahrenheit, and then moved to -70 degree Fahrenheit freezer for storage. The UCd was determined as previously described (Basu et al 2010; Srigboh et al 2016). Briefly, 0.5 mL of sample was digested with an equal volume of concentrated nitric acid and allowed to sit overnight in a fume hood.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 0.5 mL of sample was digested with an equal volume of concentrated nitric acid and allowed to sit overnight in a fume hood. The following morning Milli-Q water was carefully added to the digest to bring the acid content to 2% (Srigboh et al 2016). The digest was analyzed for Cd using an Inductively Coupled Plasma Mass Spectrometer (ICPMS; Varian 820MS).…”
Section: Methodsmentioning
confidence: 99%
“…Our study is one of the first to evaluate the impacts of metals exposures on renal damage and genetic instability markers among informal e-waste recycling workers, and one of the first to evaluate body burden of metals among e-waste recycling workers in Thailand. With a mean age of 46 years, our sample of e-waste recycling workers was older than those of many other studies; [23][24][25] with the sample roughly split between men and women, it was also more sex-balanced than many studies. While both men and women in this study appeared to do similar e-waste recycling work, we found significantly higher levels of blood Cd and Pb in men than women (Table 1).…”
Section: Discussionmentioning
confidence: 80%
“…e-waste recycling consists of a variety of activities, and the pattern and types of toxicants vary depending on the equipment being recycled. 1,24 Use of a holistic marker of DNA and RNA damage, such as 8-OHdG, allows for assessment of oxidative stress resulting from a variety of exposures, and as such, 8-OHdG represents a useful tool for health monitoring among e-waste recyclers to assess genetic instability (and, therefore, cancer risk) associated Health Risk in Electronic Waste Workers with their varied tasks and exposures. We observed an association between 8-OHdG and working hours in men ( Fig 2); we did not observe a similar correlation in women, suggesting that there may be sex-based differences in work-related oxidative stress.…”
Section: Take-home Messagementioning
confidence: 99%
“…Substitution of these hazardous elements in electronics manufacture is yet unfeasible despite the specialist's efforts. Therefore, protection of employees in recycling plants is an additional problem and should be considered during the design and implementation of recycling processes . Thus, the enormous environmental benefits of electronic waste recycling is opposed to high environmental risks in areas near recycling facilities.…”
Section: Introductionmentioning
confidence: 99%